Association between dietary fatty acid intake and preserved ratio impaired spirometry in U.S. adults: a population-based cross-sectional study - Liu, Xiang; Zeng, Wei; Zhou, Wangyan; Zheng, Dayang; Yang, Xu; Liao, Weijun (Frontiers in Nutrition, 2025)
BackgroundPreserved ratio impaired spirometry (PRISm) is increasingly recognized as a clinically relevant but underdiagnosed lung function abnormality. This pulmonary phenotype is clinically significant yet remains insufficiently studied. Although dietary fatty acids are known to have anti-inflammatory and immune-regulating properties, their relationship with PRISm has not been previously explored. This study aimed to evaluate the associations between intake of saturated (SFA), monounsaturated (MUFA), and polyunsaturated fatty acids (PUFA) and the prevalence of PRISm in U.S. adults.MethodsWe conducted a cross-sectional analysis using data from 9,103 adults in the 2007–2012 National Health and Nutrition Examination Survey (NHANES). Dietary intake of SFA, MUFA, and PUFA was assessed from two 24-h dietary recalls. Fatty acid variables were log-transformed and standardized. Logistic regression models were used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for the associations between fatty acid intake and PRISm, adjusting for sociodemographic, behavioral, and clinical covariates. Nonlinear relationships were examined using restricted cubic splines. A two-sided p-value <0.05 was considered statistically significant.ResultsAmong the study population (mean age 45.6 ± 15.8 years; 47.7% male), 1,362 participants (15.0%) exhibited the PRISm phenotype. In models controlling for demographic, lifestyle, and clinical variables, each standard deviation increase in SFA [0.86 (0.75–0.99)] and PUFA [0.88 (0.79–0.99)] intake was associated with a statistically significant reduction in the odds of PRISm. MUFA intake was not significantly related to PRISm. Restricted cubic spline analysis indicated no evidence of non-linearity in these associations. The inverse relationships for SFA and PUFA were also consistent across demographic and clinical subgroups.ConclusionGreater consumption of saturated and polyunsaturated fatty acids was associated with a lower prevalence of PRISm in a nationally representative adult population. These associations were consistent across key demographic and clinical subgroups. If confirmed in prospective studies, our findings may inform early dietary strategies to support pulmonary health.